PENGARUH BAURAN PERMASARAN TERHADAP KEPUTUSAN PEMILIHAN JASA - Diana Diana (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2022)
In 2016 - 2018 the number of visits to 6 poles including general surgery poly, echocardiography, eye poly, internal medicine, ENT poly, poly urology fluctuated from 11.23% to -5.23%. Fluctuations in the number of visits can be caused by several factors, one of which is consumer behavior in health service selection decisions. This study aims to determine the effect of the marketing mix on service selection decisions.This research is an analytic survey research with cross sectional approach. The population in this study were patients in 6 outpatient clinics at Jemursari Islamic Hospital in Surabaya. The number of samples is taken by quota sampling within one month.The results showed that the marketing mix at 6 Polis RSI Jemursari Surabaya with a good category of 77.5% resulted in high service selection decisions. The results of the ordinal regression test show a significance value of 0,000 which means that there is an influence of the marketing mix on the decision of choosing the Jemursari Hospital. Of the seven marketing mix elements that have the lowest influence on service selection decisions are the 47.1% price mix element, while the most influential marketing mix element is the human resource mix element with a percentage of 68.6%.The conclusion in this study is the positive influence of the marketing mix on the decision to choose outpatient services at the Jemursari Hospital in 2019.